2021
DOI: 10.1089/cyber.2020.0018
|View full text |Cite
|
Sign up to set email alerts
|

Violent Video Games and Aggression Among Young Adults: The Moderating Effects of Adverse Environmental Factors

Abstract: Research is divided on the effects of violent video games (VVGs). Some scholars claimed that VVG promotes aggression, reduces empathy, increases self-injury, and externalization, whereas others claim that a minimal or, in some cases, no traits as reported by the former is associated with playing VVGs. This study provides evidence to support claims that VVG is associated with aggressive behavior among young adults. However, the study focused more importantly on the moderating effects of adverse environmental fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…On the other hand, since an advergame mostly offers simplicity and a low level of challenge, adults would not be able to use all of their cognitive capabilities and, therefore, would feel less engaged. Eventually, a more immersed or engaged player having optimal experience would demonstrate higher purchase intention of the advertised brand as found in other mediated and information processing contexts such as smartphone advertising (Martins et al, 2019), online shopping (Ozkara et al, 2017), social commerce (Yusuf et al, 2018), fan page in social media (Rahman et al, 2018), and live streaming digital marketing (Addo et al, 2021) to name a few.…”
Section: Effects Of Gamification Format and Age Of Consumers On Purch...mentioning
confidence: 94%
“…On the other hand, since an advergame mostly offers simplicity and a low level of challenge, adults would not be able to use all of their cognitive capabilities and, therefore, would feel less engaged. Eventually, a more immersed or engaged player having optimal experience would demonstrate higher purchase intention of the advertised brand as found in other mediated and information processing contexts such as smartphone advertising (Martins et al, 2019), online shopping (Ozkara et al, 2017), social commerce (Yusuf et al, 2018), fan page in social media (Rahman et al, 2018), and live streaming digital marketing (Addo et al, 2021) to name a few.…”
Section: Effects Of Gamification Format and Age Of Consumers On Purch...mentioning
confidence: 94%
“…Zhai et al (2019) measured problematic video gaming by adapting the content of the Minnesota Impulsivity Interview to a questionnaire format, and found that problematic video gaming led to more somatic violence (e.g., more weapon carrying and fighting). Addo et al (2021) found that more time spent playing violent video games was associated with lower empathic attention, greater aggressionrelated thoughts, and higher aggressive behaviors.…”
Section: Individual Differences Studiesmentioning
confidence: 94%
“…Meanwhile, narcissistic adolescents may also perceive certain situations as threats to their self-esteem and engage in aggressive behavior to defend their perceived sense of superiority ( 10 ). People can attain highly favorable emotional encounters by engaging in violent activities in online games without facing consequences, potentially leading to a diminished perception of the negative impacts of aggression and an elevated inclination towards real-world aggressive behaviors ( 11 ). Moreover, once observers have confidence in themselves and believe that observed behaviors can help them achieve their goals, they will imitate those behaviors.…”
mentioning
confidence: 99%